A glance at digital forensic academic research demographics. Issue 5 (September 2020) - Horsman, Graeme; Aney Biju Mammen, Miss
Abstract: Whilst the field of digital forensics is now well established, its research community can be considered relatively emerging in comparison to the associated areas of traditional forensic and computer sciences. As a result, this comment article takes a quick look at the demographics of digital forensics research over the last 20 years, with metadata from 6589 articles being extracted and analysed from Scopus in order to provide a brief insight into this field's research activity.